Strategies to Enhance Periplasmic Recombinant Protein Production Yields in Escherichia coli - Karyolaimos, Alexandros; de Gier, Jan-Willem (Frontiers in Bioengineering and Biotechnology, 2021)
Main reasons to produce recombinant proteins in the periplasm of E. coli rather than in its cytoplasm are to -i- enable disulfide bond formation, -ii- facilitate protein isolation, -iii- control the nature of the N-terminus of the mature protein, and -iv- minimize exposure to cytoplasmic proteases. However, hampered protein targeting, translocation and folding as well as protein instability can all negatively affect periplasmic protein production yields. Strategies to enhance periplasmic protein production yields have focused on harmonizing secretory recombinant protein production rates with the capacity of the secretory apparatus by transcriptional and translational tuning, signal peptide selection and engineering, increasing the targeting, translocation and periplasmic folding capacity of the production host, preventing proteolysis, and, finally, the natural and engineered adaptation of the production host to periplasmic protein production. Here, we discuss these strategies using notable examples as a thread.